Adventures of Daniel Boom : aka Loud Boy. - Steinberg, D.J.; Illustrated by Brain Smith (New York Grosset & Dunlap, 2008)
Being the new kid in town with no volume control on his voice, Daniel Boom discovers an even bigger problem: the evil Kid-Rid Corporation has silenced the entire world with their terrible Soundsucker LX machine! Daniel taps into his inner superhero to become Loud Boy, along with his new pals who have bad habits (aka superpowers) of their own. The unlikely heroes are able to turn the tables on the villains, restoring peace and un-quiet to the world once more! But is it the end of Kid-Rid?--From Amazon.com.
Including Illustrations
Keywords: Loudness -- Boys -- Heroes